Food Security in Iceland: Present Vulnerabilities, Possible Solutions - Orri Jóhannsson 1979- (2011)
Food insecurity is a major worldwide problem. This problem is only likely to grow as food prices increases and resources get scarcer. Numerous international institutions and experts predict that conflicts over food will become more common as water and food resources become more valuable. Iceland‟s small and import oriented economy is not immune from this development and the influence of this global trend can already be felt in Iceland. Higher global food and resource prices combined with the devaluation of the Icelandic Króna have already made food imports more difficult for Iceland. This has prompted debate on the subject of food security and the value of strong domestic food production, although this discussion has not yet spread through society as a whole. Based on extensive research into economic data, consultation with experts and conducting a questionnaire among the public, this thesis attempts to shed light on the country‟s food situation, its vulnerabilities, and its strengths. Questions are asked about how Iceland stands in this regard and what threats and risks potentially endanger the food security of the nation. The state of preparedness (or lack thereof) within the administration is examined and questions are asked about what Iceland could do to improve in this area. The general findings are that the Icelandic authorities have no comprehensive contingency plans for food security and no plans for emergency food reserves. Finally, suggestions are made about areas for improvement so that food security can be safeguarded. Fæðuóöryggi er mikið vandamál í heiminum. Umfang vandans á aðeins eftir að aukast þar sem matvælaverð fer hækkandi og öll aðföng verða stöðugt erfiðari. Fjöldi alþjóðastofnana og sérfræðinga spá því að vopnuð átök vegna deilna um vatn og matvæli eigi eftir að verða algengari þar sem slíkur varningur verður sífellt verðmætari. Smár og innflutningsmiðaður efnahagur Íslands er ekki ónæmur fyrir þessari hnattrænu þróun og áhrif hennar má þegar finna á Íslandi. Hærra matvæla- og ...